Comparison of mechanical and chemomechanical methods of caries removal in deciduous and permanent teeth: A SEM study - A Avinash; S D Grover; M Koul; M T Nayak; A Singhvi; R K Singh (Wolters Kluwer Medknow Publications, 2012)
Background: Mechanical method of caries removal is associated with the removal of sound tooth structure, production of pain, heat, annoying sounds, and vibrations. Chemomechanical caries removal method is based on removal of only carious dentin leaving sound dentin intact. Aim: The aim of this study was to compare the efficacy of mechanical and chemomechanical methods of caries removal in deciduous and permanent teeth. Study Design: A total of 30 carious teeth including 15 deciduous and 15 permanent teeth having dentinal caries selected randomly and cut into two halves through center of the lesion, were subjected to caries removal by mechanical (Group A), and chemomechanical methods (Group B). Time taken for removal of caries was noted with stopwatch. Samples were prepared and seen under the scanning electron microscope for the presence of bacterial colonies. Data were analyzed using statistical package for social sciences (SPSS) Software. Results: No significant difference was found for the presence of bacterial colonies in both groups of deciduous and permanent teeth; however, time taken for caries removal by the chemomechanical method was twice than the mechanical method. Conclusion: despite the insignificant presence of bacterial colonies and twice time taken as compared to mechanical method, chemomechanical method was easy to introduce, was painless, did not form smear layer and conserved the sound tooth structure.